Exploring the interplay of T cell receptor-V gene copy numbers and major histocompatibility complex selection pressure in avian species: Insights into immune system evolution and reproductive investment - Lin Sun; Chunhong Liang; Shidi Qin; Ying Zhu; Ke He (Avian Research)
Birds, a fascinating and diverse group occupying various habitats worldwide, exhibit a wide range of life-history traits, reproductive methods, and migratory behaviors, all of which influence their immune systems. The association between major histocompatibility complex (MHC) genes and certain ecological factors in response to pathogen selection has been extensively studied; however, the role of the co-working molecule T cell receptor (TCR) remains poorly understood. This study aimed to analyze the copy numbers of TCR-V genes, the selection pressure (ω value) on MHC genes using available genomic data, and their potential ecological correlates across 93 species from 13 orders. The study was conducted using the publicly available genome data of birds. Our findings suggested that phylogeny influences the variability in TCR-V gene copy numbers and MHC selection pressure. The phylogenetic generalized least squares regression model revealed that TCR-Vαδ copy number and MHC-I selection pressure were positively associated with body mass. Clutch size was correlated with MHC selection pressure, and Migration was correlated with TCR-Vβ copy number. Further analyses revealed that the TCR-Vβ copy number was positively correlated with MHC-IIB selection pressure, while the TCR-Vγ copy number was negatively correlated with MHC-I peptide-binding region selection pressure. Our findings suggest that TCR-V diversity is significant in adaptive evolution and is related to species’ life-history strategies and immunological defenses and provide valuable insights into the mechanisms underlying TCR-V gene duplication and MHC selection in avian species.